Proceedings of the Third International Conference on Sustainable Innovation 2019 – Health Science and Nursing (IcoSIHSN 2019) 2019
DOI: 10.2991/icosihsn-19.2019.19
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of The Use of Cervical Cancer Prevention Guideline Book on Women Participation in Visual Inspection with Acetic acid (VIA)

Abstract: Cervical cancer is the second leading cause of death for women in the world after breast cancer. It is estimated that every 40-45 new cases occur and around 20-25 people die due to cervical cancer. In Kudus , the coverage of early detection of cervical cancer by the VIA method is only 2% of the number of women aged 30-50 years. This study aims to determine the effectiveness of health promotion and guidebook on the early detection of cervical cancer as an effort to increase the participation in women's VIA exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…If women, especially mothers, get enough knowledge about the dangers of cervical cancer and the benefits of IVA examination, they will realize the importance of early detection and prevention. Until now, most Indonesian people, especially women, are still relatively unfamiliar with the importance of Visual Inspection with Acetic acid (IVA) or pap smears to detect the possibility of having cervical cancer early [3] .…”
Section: Introductionmentioning
confidence: 99%
“…If women, especially mothers, get enough knowledge about the dangers of cervical cancer and the benefits of IVA examination, they will realize the importance of early detection and prevention. Until now, most Indonesian people, especially women, are still relatively unfamiliar with the importance of Visual Inspection with Acetic acid (IVA) or pap smears to detect the possibility of having cervical cancer early [3] .…”
Section: Introductionmentioning
confidence: 99%
“…One of which is social cultural factors, if these factors have been embedded and internalized in people's lives and activities exist tendency to change behaviors has been formed is difficult to done. To overcome and understand Health problems require knowledge adequate, so deep socialize health on wider community can be more directed [9] Many factors related to the participation of mothers to participate in the IVA test include behavioral factors that are influenced by the intentions and attitudes of mothers. Based on the results of the study showed that women who behave well have greater potential to undergo IVA examination when compared with women who behave less well.…”
Section: Introductionmentioning
confidence: 99%